FUNGSI LIPSCHITZIAN SERAGAM DI RUANG METRIK DENGAN STRUKTUR NORMAL SERAGAM - , MUHAMAD NAJIBUFAHMI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this thesis, we discuss the sufficient conditions for the existence of fixed points of uniformly Lipschitzian mappings in metric spaces with uniform normal structure. We also discuss the sufficient conditions on the fixed point theorem for uniformly Lipschitzian mappings in hyperconvex spaces. In the last section weconstruct a property to ensure the existence of fixed points of continuous nearly uniformly Lipschitzian mappings in metric spaces with uniform normal structure under some conditions.